PREDICTION OF EROSION BY THE METHOD OF USLE (UNIVERSAL SOIL LOSS EQUATION) - Martha Fera Garing; Edy F. Lengkong (Jurnal Agroekoteknologi Terapan, 2021)
Soil as a natural resource has been subjected to various pressure along with an increase in the number of human beings. Such pressure has led to a decrease in the quality of the soil that leads to the reduction of the soil's ability to produce. A decrease in the quality of the soil is caused by the process of leaching of nutrients and the process of soil erosion, especially on land - land that does not have closing vegetation. Erosion is the events of emigration land or portions of land from one place to another by nature. Erosion in the event, the ground or parts of the land eroded and transported, are then deposited in other places.Keywords =    erosion; soil. AbstrakTanah sebagai sumber daya alam telah mengalami berbagai tekanan seiring dengan peningkatan jumlah manusia. Tekanan tersebut telah menyebabkan penurunan mutu tanah yang berujung pada pengurangan kemampuan tanah untuk berproduksi. Penurunan mutu tanah disebabkan oleh proses pencucian hara dan proses erosi tanah terutama pada lahan- lahan yang tidak memiliki penutupan vegetasi. Erosi adalah peristiwa pindahnya atau terangkutnya tanah atau bagian-bagian tanah dari suatu tempat ke tempat lain oleh media alami. Pada peristiwa erosi, tanah atau bagian- bagian tanah terkikis dan terangkut, kemudian diendapkan di tempat lain.Kata kunci =   pengikisan; tanah.